Creating Your Own Angel Investor Group : A Guide for Emerging and Frontier Markets - World Bank (Washington, DC, 2015)
In little more than a decade, formal angel investing organizations have shifted from being mostly a United States (U.S.) and European phenomenon to being active and visible around the world. From Colombia to Cambodia, Serbia to South Africa, angel investors build networks from scratch and put their own local spin on how these networks are founded, structured, and operated. However, for every successful angel group founder there are many more potential founders looking for a place to start. This guidebook aims to support such individuals and newly formed angel groups by presenting global best practices and tools and templates for facilitating group operations.